(untitled) (Journal of the College of Basic Education, 2022)
A field experiment was conducted for the summer season 2012 to study the effect of drought stressSpraying with aspirin on some phenotypic, physiological and yield traits of maize(264 710 5); Drought stress treatments were irrigate every other day; Irrigate every 7 days and irrigate every4 days; The concentrations of aspirin are 0 030 70 ppm. The results showed that the effect ofDrought stress with spacing of irrigation periods led to a significant decrease in the rates of traitsstudied; As for the effect of spraying with aspirin, the results showed a significant increase in most ratesThe studied traits, especially when the concentration was 30 ppm, the plant height increased by7, leaf number 6.46%, dry weight 48.52%, and chlorophyll content9 For leaf area 9.11%, proline content 968.27, and number of earwigs6. The number of grains is 19.43%, the weight of the grain is 23.45%, and the percentage of oil7 compared to control plants.